NILAI BUDAYA DALAM TRADISI ARAK-ARAKAN PENGANTIN MELAYU PONTIANAK - reren alfathia sahara; Dr. Gunta Wirawan; Lili Yanti, S.Pd., M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reren Alfathia : Cultural Values in the Malay Wedding Procession Tradition of Pontianak. Thesis, ISBI Singkawang 2025. This study aims to describe the cultural values embedded in the traditional wedding procession (arak-arakan) of the Malay community in Pontianak. The research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that this tradition reflects various cultural values such as religious values, mutual cooperation and kinship, aesthetics, cultural identity, and educational values. These values are manifested in the procession, symbols, traditional attire, ceremonial rhymes (pantun antarbarang), and the active involvement of the community. The tradition not only serves as a wedding ceremony but also functions as a medium for cultural preservation and character education for the younger generation. Therefore, the Malay wedding procession tradition in Pontianak plays an important role in strengthening local cultural identity and enhancing social cohesion. Keywords : Cultural Values, procession traditions, Malay brides, Pontianak, local wisdom.